Practical course supporting English language learning for the 1st year students, semester 1 (all training programs) электронный курс - Денико, Р. В. лингвист доцент Томского политехнического университета, кандидат филологических наук 1986- (TPU Moodle, 2020)
The course is intended for developing listening, reading, writing and speaking skills, revising grammar material and increasing vocabulary on the topics concerned. The course is developed for learning English for General Purposes by the first year students of TPU, 1st semester. The required level of English is A1-B1. The course is intended for 18 hours.